Tramadol intoxication in infants: experience at a tertiary care hospital in Dhaka, Bangladesh (BIRDEM Medical Journal, 2021)
Background: Tramadol is a widely used opioid analgesic for different types of pain. Very few cases of acute tramadol intoxication in infants have been reported where respiratory and central nervous system depression are frequent. The aim of this study was to evaluate the clinical manifestation, treatment and outcome of tramadol intoxication in infants.Methods: This was a retrospective observational study of hospitalized infants in the Department of Neonatology and Paediatrics in BIRDEM General Hospital, Dhaka, Bangladesh from February 2014 to November 2019. Ten infants with history of administration of tramadol suppository were included in this study. Data regarding clinical features, cause of the “incident dose and route of administration” of tramadol, effects of naloxone and outcomes were recorded and analyzed.Results: Of 10 infants, 6 were male and 4 were female. The mean age was 5.1±3.0 months and the mean weight was 6.1±1.8 kg. The mean time of onset of symptoms after drug administration was 2.6±1.0 hours with a mean dose of 17.9±6.4 mg/kg body weight. The main clinical features were decreased level of consciousness (100%), seizure (80%), meiosis (80%) and apnoea (50%). In each 50% (5) of cases, tramadol was given erroneously instead of glycerine and paracetamol suppository. Among them 2 (20%) infants received tramadol suppository as an over-the-counter (OTC) drug. All infants were treated with naloxone without any side effect. In addition, three infants needed mechanical ventilation. The average duration of hospital stay was 89.3±47.4 hours. Nine infants were discharged and one (10%) died.Conclusions: Our study suggested that tramadol intoxication among infants is predominantly accidental. Early identification and prompt initiation of treatment are essential. The creation of public awareness about the safe storage of drugs at home and avoidance of OTC drugs can prevent tramadol intoxication in children.BIRDEM Med J 2021; 11(3): 197-201